Salvage radiotherapy with or without short-term hormone therapy for rising prostate-specific antigen concentration after radical prostatectomy (GETUG-AFU 16): a randomised, multicentre, open-label phase 3 trial. Issue 6 (June 2016) - Carrie, Christian; Hasbini, Ali; de Laroche, Guy; Richaud, Pierre; Guerif, Stéphane; Latorzeff, Igor; Supiot, Stéphane; Bosset, Mathieu; Lagrange, Jean-Léon; Beckendorf, Véronique; Lesaunier, François; Dubray, Bernard; et al.
Summary: Background: How best to treat rising prostate-specific antigen (PSA) concentration after radical prostatectomy is an urgent clinical question. Salvage radiotherapy delays the need for more aggressive treatment such as long-term androgen suppression, but fewer than half of patients benefit from it. We aimed to establish the effect of adding short-term androgen suppression at the time of salvage radiotherapy on biochemical outcome and overall survival in men with rising PSA following radical prostatectomy. Methods: This open-label, multicentre, phase 3, randomised controlled trial, was done in 43 French study centres. We enrolled men (aged ≥18 years) who had received previous treatment for a histologically confirmed adenocarcinoma of the prostate (but no previous androgen deprivation therapy or pelvic radiotherapy), and who had stage pT2, pT3, or pT4a (bladder neck involvement only) in patients who had rising PSA of 0·2 to less than 2·0 μg/L following radical prostatectomy, without evidence of clinical disease. Patients were randomly assigned (1:1) centrally via an interactive web response system to standard salvage radiotherapy (three-dimensional [3D] conformal radiotherapy or intensity modulated radiotherapy, of 66 Gy in 33 fractions 5 days a week for 7 weeks) or radiotherapy plus short-term androgen suppression using 10·8 mg goserelin by subcutaneous injection on the first day of irradiation and 3 months later. Randomisation was stratified using a permuted block method according to investigational site, radiotherapy modality, and prognosis. The primary endpoint was progression-free survival, analysed in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, number NCT00423475 . Findings: Between Oct 19, 2006, and March 30, 2010, 743 patients were randomly assigned, 374 to radiotherapy alone and 369 to radiotherapy plus goserelin. Patients assigned to radiotherapy plus goserelin were significantly more likely than patients in the radiotherapy alone group to be free of biochemical progression or clinical progression at 5 years (80% [95% CI 75–84] vs 62% [57–67]; hazard ratio [HR] 0·50, 95% CI 0·38–0·66; p<0·0001). No additional late adverse events occurred in patients receiving short-term androgen suppression compared with those who received radiotherapy alone. The most frequently occuring acute adverse events related to goserelin were hot flushes, sweating, or both (30 [8%] of 366 patients had a grade 2 or worse event; 30 patients [8%] had hot flushes and five patients [1%] had sweating in the radiotherapy plus goserelin group vs none of 372 patients in the radiotherapy alone group). Three (8%) of 366 patients had grade 3 or worse hot flushes and one patient had grade 3 or worse sweating in the radiotherapy plus goserelin group versus none of 372 patients in the radiotherapy alone group. The most common late adverse events of grade 3 or worse were genitourinary events (29 [8%] in the radiotherapy alone group vs 26 [7%] in the radiotherapy plus goserelin group) and sexual disorders (20 [5%] vs 30 [8%]). No treatment-related deaths occurred. Interpretation: Adding short-term androgen suppression to salvage radiotherapy benefits men who have had radical prostatectomy and whose PSA rises after a postsurgical period when it is undetectable. Radiotherapy combined with short-term androgen suppression could be considered as a reasonable option in this population. Funding: French Ministry of Health, AstraZeneca, and La Ligue Contre le Cancer.